Implementation of Islamic Business Ethics in Padang Restaurant Businesses in Ambon City - Nirmala Mada Ali; Yusdiman Yusdiman; Kamala Soleman; Reza Abdulmudy (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the implementation of Islamic business ethics in Padang restaurants in Ambon City and their compliance with Islamic business ethics principles. The study used a qualitative descriptive method with a purposive approach and theoretical sampling. The research informants consisted of owners, employees, and customers from six Padang restaurant businesses: Ayah Restaurant, Ayah Kembar Restaurant (two locations), Nusantara Restaurant (two locations), and Putra Minang Restaurant. Data collection techniques included in-depth interviews, direct observation, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that the four characteristics of the Prophet Muhammad (peace be upon him): shiddiq (honest), amanah (trustworthy), fathanah (intelligent), and tabliqh (communicative) have been internalized by the restaurant owners and taught to employees. Honesty is the main foundation in product management, amanah is realized through responsibility and service, fathanah is reflected in business strategies and knowledge, and tabliqh is implemented through friendly and polite communication. In terms of product quality and service, all restaurants demonstrated adherence to the principles of halal certification, cleanliness, freshness, and hospitality. This study concluded that Islamic business ethics have been substantially implemented in Padang restaurants in Ambon City, although there is still room for improvement, particularly in documentation and consistency.